The role of school management committee in improving students' academic performance in Tanzania: A case of ward secondary schools in Ubungo district, Dar-es-salaam - Longino, Teddy (Mzumbe University, 2024)
A Dissertation submitted in partial fulfillment of the requirements for award of the Degree of Master of Leadership and Management (MLM) of Mzumbe University.